Approach to residual dizziness after successfully treated benign paroxysmal positional vertigo: effect of a polyphenol compound supplementation - Casani, Augusto Pietro (Clin Pharmacol, 2019)
PURPOSE: To assess if a polyphenol compound supplementation (Vertigoval(®)) could improve residual dizziness earlier after benign paroxysmal positional vertigo (BPPV) and relieve patients from this disabling symptomatology. METHODS: In this prospective, multicentric study, 127 patients were randomized in the treatment group (TG), who received a 60-day supplementation, while 131 patients were randomized in the control group (CG), who did not receive any medication. The dizziness handicap inventory (DHI) score, static posturography, and the visual analog scale (VAS) for both dizziness (D-VAS) and nausea/vomit (N/V-VAS) were used as measures of outcome at baseline and after 30 and 60 days. Patients were asked about efficacy and tolerance to the treatment. Side effects were examined. RESULTS: A statistically significant greater decrease was established in the TG for DHI, D-VAS, and N/V-VAS compared to the CG. On the other hand, static posturography did not show statistical differences between the two groups, though a better clinical improvement after 60-day supplementation was shown in the TG in comparison to the CG. We counted mild side effects in only 2 patients. Most patients reported an excellent or good efficacy and tolerance to the treatment. CONCLUSION: Residual dizziness is a frequent condition of unknown origin that manifests as persistent disabling imbalance after successful repositioning maneuvers for BPPV. The decreasing postural control can affect the quality of life, contributing to falling and psychological problems. The supplementation with the polyphenol compound used in our study is safe, manageable, and appeared to be able to reduce subjective symptoms and improve instability earlier, decreasing the risk of potential complications.